Disruption of gene expression in hybrids of the fire ants Solenopsis invicta and Solenopsis richteri - LINO OMETTO; KENNETH G. ROSS; DeWAYNE SHOEMAKER; LAURENT KELLER (Molecular Ecology, 2012)
Transcriptome analysis is a powerful tool for unveiling the distribution and magnitude of genetic incompatibilities between hybridizing taxa. The nature of such incompatibilities is closely associated with the evolutionary histories of the parental species and may differ across tissues and between the sexes. In eusocial insects, the presence of castes that experience divergent selection regimes may result in additional distinct patterns of caste‐specific hybrid incompatibilities. We analysed levels of expression of >14 000 genes in two life stages of each caste in the fire ants Solenopsis invicta and Solenopsis richteri and in their hybrids. We found strong contributions of both developmental stage and caste to gene expression patterns. In contrast, variability in expression was only weakly associated with taxonomic identity, with hybrid scores falling between those of the two parental species. Hybrid incompatibilities were surprisingly modest, with only 32 genes being mis‐expressed, indicating low levels of disruption in gene regulation in hybrids; males and workers each mis‐expressed at least seven times as many genes as queens. Interestingly, homologues of many of the mis‐expressed genes have been implicated in behavioural variation in Drosophila melanogaster . General expression profiles of hybrids consistently were more similar to those of S. richteri than S. invicta , presumably because S. richteri trans ‐regulatory elements tend to be dominant and/or because there is an overall bias in the genetic composition of the hybrids towards S. richteri. Altogether, our results suggest that selection acting on each caste may contribute differently to interspecific divergence and speciation in this group of ants.